(untitled) (FULafia Journal of Science and Technology, 2018)
A motorized jul/nice extractor was designed, fabricated and evaluated with orange, pineapple and golden melon fruits. The major components of the extractor included the hopper, slicing chamber, extracting chamber, frame and outlets for juice and pulp. The machine was powered by a 2 h.p. electric motor. The results of the evaluation showed a fruit yield of 38.00, 51.43 and 39.67% for orange, pineapple and golden melon respectively and extraction efficiency of 65.47, 83.94 and 53.17% for the three fruits respectively while the juice extraction loss was 6, 9 and 28% respectively for the three fruits. The cost of producing the machine is N 58,130 (USD 161.47) which makes it affordable to small scale fruit juice producers